2015
DOI: 10.1177/2211068214563794
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis and Management of Hepatitis C Virus Infection

Abstract: The hepatitis C virus (HCV) infects more than 200 million people globally, with increasing incidence, especially in developing countries. HCV infection frequently progresses to chronic liver disease, creating a heavy economic burden on resourcepoor countries and lowering patient quality of life. Effective HCV diagnosis, treatment selection, and treatment monitoring are important in stopping disease progression. Serological assays, which detect anti-HCV antibodies in the patient after seroconversion, are used f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
20
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(25 citation statements)
references
References 91 publications
(141 reference statements)
3
20
0
2
Order By: Relevance
“…13 The measurement of viral load is a key predictive factor that can be employed to develop successful treatment interventions. 8 In the present study, as reported in previous works, 14,15 genotype 3 followed by genotype 1, were the most prevalent genotypes. The maximum levels of HCV viremia were detected in the mixed genotype group, and the lowest levels were found in the undetectable genotype group.…”
Section: Discussionsupporting
confidence: 83%
See 3 more Smart Citations
“…13 The measurement of viral load is a key predictive factor that can be employed to develop successful treatment interventions. 8 In the present study, as reported in previous works, 14,15 genotype 3 followed by genotype 1, were the most prevalent genotypes. The maximum levels of HCV viremia were detected in the mixed genotype group, and the lowest levels were found in the undetectable genotype group.…”
Section: Discussionsupporting
confidence: 83%
“…The early identification and effective management of the infection could be changing the natural progression of the disease . The measurement of viral load is a key predictive factor that can be employed to develop successful treatment interventions . In the present study, as reported in previous works, genotype 3 followed by genotype 1, were the most prevalent genotypes.…”
Section: Discussionsupporting
confidence: 78%
See 2 more Smart Citations
“…In spite of the high prevalence of disease and new opportunities for access to direct acting antiviral treatment, most people are unaware of their infection [37]. The presence of HCV RNA in peripheral blood is a reliable diagnostic marker for HCV infection; it can be detected prior to seroconversion to diagnose acute infection, distinguish active from resolved infections, and identify patients with chronic HCV that lack an antibody response such as patients on hemodialysis or those co-infected with HIV [3840]. …”
Section: Discussionmentioning
confidence: 99%